Pengaruh Kualitas Produk terhadap Kepuasan Konsumen TCR Sablon - Hapsari Widayani; Chandra Fasih (Neolectura, 2021)
This study aims to determine the effect of product quality on TCR Sablon consumer satisfaction and promotional media and also to assist in developing the TCR Sablon business. This research method used quantitative research methods. Data collection methods used by the author are questionnaires, interviews and literature study. After the data was obtained from interviews and questionnaires, then it was processed into statistical data with the determined sample being 41 consumers of TCR Sablon. The result of this research is that there is a positive and significant influence between product quality and TCR Sablon consumer satisfaction. This can be seen in the results which show that the reliability test analysis of the product quality variable (variable X) shows the results obtained are 0.9513 and the consumer satisfaction variable (variable Y) is 0.7938, both of which qualify the test requirements. reliability, that is, it exceeds the significant value of = 0.05 of 0.3081. Simple linear regression test obtained results of Y = 55.685 + 0.326X and correlation coefficient analysis obtained results of 0.569 so that it was concluded that there was a strong relationship between the two variables.